College Algebra (6th Edition)

Published by Pearson
ISBN 10: 0-32178-228-3
ISBN 13: 978-0-32178-228-1

Chapter P - Prerequisites: Fundamental Concepts of Algebra - Exercise Set P.3: 114


${x^{-2}y^{2}}$ = $\frac{y^{2}}{x^{2}}$

Work Step by Step

$(\frac{x^{\frac{1}{2}}y^{-\frac{7}{4}}}{y^{-\frac{5}{4}}})^{-4}$ = $({x^{\frac{1}{2}}y^{-\frac{7}{4} +\frac{5}{4}}})^{-4}$ = $({x^{\frac{1}{2}}y^{-\frac{2}{4}}})^{-4}$ = $({x^{\frac{1}{2}\times-4}y^{-\frac{2}{4}\times-4}})$ = $({x^{-2}y^{2}})$ = $\frac{y^{2}}{x^{2}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.